Classroom’s Environment and FOMO: Students’ Perspectives - Arrisma Delimasari; Nisrina Fauziah; Dhania Puspita Anjarsari; Taufik Arochman (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
The level of concentration is one of the things that is important in the learning process since it can determine whether the students understand the learning material being taught or not. Therefore, this study was conducted with the aim of finding out what factors can influence students' learning concentration, especially in terms of the classroom situation and the sense of FOMO they might feel, as well as how students overcome this sense of FOMO when doing assignments. In order to obtain the required data, the researcher used a qualitative research method and shared questionnaires to fourth semester English Education students at Universitas Tidar. From the questionnaire that was filled in by 47 students, it was found that the noisy, boring class and when students were sleepy were the class situation that could affect their learning concentration. In addition, the feeling of FOMO also affects their concentration, especially when students know that their friend had done the task, while the student had not. The effect is that this can slow down student development, because when doing assignments students would seem in a hurry because they wanted to finish quickly without really understanding the material.